Impact of Anchor Characteristics on Impulsive Buying Among Generation Z in Live Streaming on Short-Form Video Apps: The Moderating Role of Gender - SIOW, XIU JING; PHANG, ING GRACE (International Journal of Electronic Commerce Studies, 2025)
In live-streaming commerce, anchors play a pivotal role in driving sales. Grounded in the Stimulus-Organism-Response (S-O-R) model, this study examines how anchor characteristics—attractiveness, expertise, and trustworthiness—influence Generation Z's urge to buy impulsively. Data was collected from 272 Malaysian Generation Z consumers with live-streaming shopping experiences and analyzed using SmartPLS 4. The findings reveal that anchor characteristics significantly impact consumer arousal and the urge to buy impulsively. Additionally, the influence of arousal on impulse buying is stronger among women than men. However, this study has a limitation in terms of gender imbalance in the sample (82.7% female vs. 17.3% male), which may affect the generalizability of gender-based findings. Despite this limitation, this study enhances the understanding of online impulsive buying among Generation Z, providing scholars and marketers with valuable insights into this young consumer group's live-streaming purchasing behavior. Keywords: Live-streaming, Short-Form Video Apps, Generation Z, Anchor, Impulsive Buying Intention